COMPARATIVE STUDIES OF THE CONTENT OF ANTIOXIDANTS IN FRUITS OF SOME AUTOCHTHONOUS CHERRY VARIETIES - Ana Selamovska; Viktor Gjamovski; Milena Taseska-Gjorgjijevski; Dushko Nedelkovski; Katerina Bandjo Oreshkovikj; Biljana Korunovska; Roze Gjolevska-Millenkovska (Goce Delcev University of Štip, 2022)
The content of vitamin C, total phenols, anthocyanins, flavan-3-ols and the fruit antioxidant activity of 6 cherry varieties (Ohridska brza, Ohridska rana, Ohridska crna, Dolga shishka, Dalbazlija and Ohridska bela) was examined. The fruits of autochthonous cherry varieties (Prunus avium L.) averagely contained 12.83 mg% vitamin C, 1386.25 mg/kg FW total phenols, 394.30 mg/kg FW anthocyanins, 69.150 mg/kg FW flavan-3-ols and had antioxidant activity 43.36% inhibition. Some of the autochthonous cherry varieties compared to the proposed standard variety showed higher values in the examined parameters. The highest content of vitamin C and the fruit antioxidant activity were recorded in Dalbazlija and Dolga shishka varieties. The highest content of total phenols had the standard variety Burlat. High content of total phenols was also found in Ohridska rana, Dalbazlija, Ohridska brza and Ohridska crna varieties. Ohridska rana and Ohridska crna varieties had higher content of anthocyanins compared to the standard variety and other autochthonous varieties. A moderate positive correlation was found between the content of anthocyanins and vitamin C. There was a moderate negative correlation between the content of flavan-3-ols and phenols. A very high positive correlation was found between the content of vitamin C and the antioxidant activity, while other chemical compounds had little or no effect on the antioxidant activity of cherry fruits.
Keywords: Prunus avium L., vitamin C, total phenols, anthocyanins, flavan-3-ols, antioxidant activity